2018
DOI: 10.1155/2018/4107590
|View full text |Cite
|
Sign up to set email alerts
|

Computer Vision Syndrome and Associated Factors among Computer Users in Debre Tabor Town, Northwest Ethiopia

Abstract: Background Globally, computer is one of the common office tools used in various institutions. Using computer for prolonged time led to the users at greater health risk of computer vision syndrome (CVS). Computer vision syndrome is the leading occupational health problem of the twenty-first century. About 70 percent of computer users are suffered from CVS. Besides the health problems, CVS causes inefficiency at workplace and deteriorate quality of work. The problem of CVS and its risk factors are not well known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
107
5
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(134 citation statements)
references
References 20 publications
(38 reference statements)
11
107
5
11
Order By: Relevance
“…Headache and eyestrain were the most common symptoms of CVS among the studied population [13]. It is obvious that there was potential association between current and previous studies on how to takle heatlh problems and lead a positive life style [14].…”
Section: Original Research Articlementioning
confidence: 92%
See 1 more Smart Citation
“…Headache and eyestrain were the most common symptoms of CVS among the studied population [13]. It is obvious that there was potential association between current and previous studies on how to takle heatlh problems and lead a positive life style [14].…”
Section: Original Research Articlementioning
confidence: 92%
“…More than 120 million people here are engaged with computer work and the number of people using computer has been progressively increasing every day [3]. A Study was carried out in Jamnagar in India to ascertain whether computer professionals had Computer Vision Manuscript received: 10 th September 2018 Reviewed: 20 th September 2018 Author Corrected; 25 th September 2018 Accepted for Publication 30 th September 2018 Syndrome, in which of the 1205 professionals surveyed, nearly half of them had it owing to the computer usage. It also revealed that 70% of the computer professionals working in metropolitan cities across India had CVS [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, 89.5% students stated experiencing the symptoms of DES which is similar to that reported by Logaraj et al and Reddy et al 9,10 The prevalence of DES or CVS ranged from 53-73% in several other studies on computer users. [11][12][13][14][15][16][17] In a study in Malaysia conducted on 795 university students aged between 18 and 25 years, 89.9% of students surveyed feeling any type of symptom of DES. 10…”
Section: Prevalencementioning
confidence: 99%
“…12,18 However, various other studies on college students or computer users found a male preponderance of DES; mean age being between 21 to 25 years. 9,11,15,16,19…”
Section: Age/gendermentioning
confidence: 99%
See 1 more Smart Citation